Огляд існуючих рішень та розробка програмного забезпечення для аналізу майбутньої професійної орієнтації школярів - Кисіль, В. В. (ХНУРЕ, 2023)
The thesis is devoted to the development software product for analyzing the future professional orientation of schoolchildren. It emphasizes what the software is supposed to do. The study explores the design and functionality existing systems for analyzing the future professional orientation of schoolchildren and offers recommendations for creating new software product. The thesis delves into the selection and explanation of the choice of technologies and programming languages for software development. The research highlights new software product should be cheap, suitable for current realities and trends, adaptive, and should take into account important factors of students such as emotional intelligence